2018
DOI: 10.14569/ijacsa.2018.090523
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Winnowing Algorithm with Dictionary English-Indonesia Technique to Detect Plagiarism

Abstract: The ease of obtaining information that is easy, fast, and cheap from all over the world through the internet network can encourage someone to take action plagiarism. Plagiarism is an intellectual crime that often occurs in the writing world where the perpetrators take the work of others without declaring the original source; if it continues to be left it will have a negative impact on the academic community and can be a chronic disease in the progress of a nation. At this time, the process of plagiarism detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…The stages of the Horspool Boyer-Moore algorithm were preprocessing, needle word-trigrams formation, bad-character table formation, and haystack-needle matching. The illustration of the different stages of the Rabin-Karp, Winnowing, and Horspool Boyer-Moore algorithms [4], [14], [24], [26], [29], [30], [31], [32] in identifying similarity based on word-level trigrams is presented in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stages of the Horspool Boyer-Moore algorithm were preprocessing, needle word-trigrams formation, bad-character table formation, and haystack-needle matching. The illustration of the different stages of the Rabin-Karp, Winnowing, and Horspool Boyer-Moore algorithms [4], [14], [24], [26], [29], [30], [31], [32] in identifying similarity based on word-level trigrams is presented in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Winnowing algorithms as methods to identify word similarities between scientific work documents, the previous studies related to the application of both algorithms showed excellent results, either using in mono-language or multi-language forms and even using Chinese and Arabic letters [5], [9], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…Rolling hash adalah metode yang digunakan untuk mencari nilai hash dari gram yang telah dibentuk. Nilai hash adalah nilai numerik yang terbentuk dari kode ASCII (Yudhana et al, 2018) Formu rolling hash sebagai berikut: Gambar 2. Flowchart proses pengolahan data Sebelum menghasilkan nilai kesamaan dan waktu proses, kunci jawaban dan jawaban mahasiswa terlebih dahulu melalui pre-prosesing dan selanjutnya diproses menggunakan algoritma winnowing untuk menghasilkan fingerprint.…”
Section: A) Rolling Hashunclassified
“…Pembentukan gram menggunakan character-level trigrams dan pengukuran similaritas menggunakan rumus Jaccard Coefficient. Hasil penelitian menunjukkan bahwa algoritma Winnowing dapat mendeteksi kesamaan teks dengan hasil sebesar 45,21% [5].…”
Section: Pendahuluanunclassified